Assessment on the ASEAN standards to support sustainable and responsible investments (SRIs) and green bonds / Muhammad Zarunnaim Wahab and Asmadi Mohamed Naim - Wahab, Muhammad Zarunnaim; Mohamed Naim, Asmadi (Universiti Teknologi MARA, 2021)
This paper aims to analyse the standards in promoting sustainable and responsible investment (SRIs) and green bonds among ASEAN countries. Thus, to progressively reach these objectives, this paper applied content document analysis and expert interviews. This paper discusses in detail the three ASEAN's standards issued by the ASEAN Capital Markets Forum (ACMF) to support SRIs and green bonds, namely the ASEAN Green Bond Standards 2017, the ASEAN Social Bond Standards 2018 and the ASEAN Sustainability Bond Standards 2018. Besides, this paper also explores the strengths and the weaknesses of the issuances of these ASEAN standards. The limitations of this research are that it is entirely conceptual, and its' analysis is based on secondary data sources.